Influence of size on total mercury (THg), methyl mercury (MeHg), and stable isotopes of N and C in green turtles (Chelonia mydas) from NE Brazil. - Rodriguez, César Augusto Barrios (2020)
The green turtle (Chelonia mydas) is known to present an herbivorous diet as an adult; however, juveniles may have an omnivore habit, and these changes in food preference may affect the uptake and accumulation of pollutants, such as mercury (Hg). In order to better understand the influence of this ontogenetic shift on Hg accumulation, this study evaluates the concentrations of total mercury (THg), methyl mercury (MeHg), and stable isotopes of carbon and nitrogen (δ13C and δ15N) in a group of juveniles of the green turtle. Tissue samples (liver, kidney, muscle, and scutes) were sampled from 47 turtles stranded dead on the coast of Bahia, NE, Brazil, between 2009 and 2013. The turtles analyzed showed a size range of 24.9–62.0 cm and an average of 36.4 ± 7.2 cm of curved carapace length. The scutes showed to be a viable method for Hg monitoring in the green turtles. The concentrations of THg and MeHg decreased with increasing size. The isotope values of δ15N and δ13C did not show a clear relationship with the size, suggesting that the green turtles used in our work would be occupying similar trophic levels, and foraging habitat. Keywords Chelonia mydas . Mercury . MeHg . Carbon isotope . Nitrogen isotope . Green turtle . SIA